The 2021 Madrilenian regional election: how can the incumbent improve its results in times of crisis? - Coulbois, Jaime (Frontiers in Political Science, 2023)
Although there is a considerable amount of work on the effect of catastrophes on elec-tions, we still do not have much work on the impact of the COVID-19 pandemic on them. This paper focuses on the case of the Madrilenian regional election of 2021, looking for the causes of the improvement of the ruling party’s results, the Popular Party (PP), which went from having 22.23% of the vote share in 2019 to 44,76% in 2021, and more concretely to the role that COVID-19 had on this. This election is es-pecially interesting for this matter because the main issue was the question of how to manage the pandemic: the right-wing parties (and mainly the PP) criticized the re-strictions imposed by the central government, led by the socialist Pedro Sánchez, while the left-wing parties defended them. Using separate analyses at the aggregate and indi-vidual levels, the article shows that the main factors behind the PP's improvement were the absorption of its main competitor, Ciudadanos, the mobilization of previously ab-stentionist voters, and the impact of COVID-19 itself, with a higher propensity to in-crease their vote for the PP in the most affected areas. The paper contributes therefore to the understanding of the electoral consequences of the pandemic, providing some evidence that in this case there was a rejection of the restrictions.